C-Geranylated Flavanones from Paulownia tomentosa Fruits as Potential Anti-inflammatory Compounds Acting via Inhibition of TNF-α Production - Hanáková, Zuzana; Hošek, Jan; Babula, Petr; Dall'Acqua, Stefano; Václavík, Jiří; Šmejkal, Karel (Journal of natural products, 2015)
Eleven new C-geranylated flavonoids, tomentodiplacones L, M, and N (1, 2, 10), tomentodiplacol B (3), 3',4'-O-dimethyl-5'-hydroxydiplacone (4), mimulones F, G, and H (5, 6, 7), paulowniones A (8) and B (9), tomentone (11), and 3',4',5'-trimethoxyflavanone (12), together with 11 known flavonoids (13-23), were isolated from fruits of Paulownia tomentosa. The structures of the compounds isolated were determined by spectroscopic data interpretation. The ability of compounds 1-23, together with the nonprenylated flavanones eriodictyol (24) and naringenin (25), to reduce the production of the pro-inflammatory cytokine TNF-α in THP-1 cells after bacterial lipopolysaccharide stimulation was evaluated using an in vitro screening test. The preliminary structure-activity relationships of these derivatives were also studied, and the correlation of their TNF-α inhibitory activity with their lipophilicity was investigated. The mechanism of action of compounds with significant antiphlogistic potential (4, 7, 10, 14, 22) was investigated. These compounds reduced both the secretion of TNF-α and the level of its corresponding mRNA. Compounds 4, 7, 10, 14, and 22 inhibited the nuclear translocation of NF-κB, which controls the expression of TNF-α, by blocking the degradation of IκB.
Keywords: Lipopolysaccharides; Tumor Necrosis Factor-alpha; Structure-Activity Relationship; lipopolysacharidy; Česká republika; molekulární struktura; Molecular Structure; I-kappa B Proteins; Models, Biological; Flavanones; vztahy mezi strukturou a aktivitou; Czech Republic; ovoce; biologické modely; NF-kappa B; proteiny I-kappa B; Magnoliopsida; TNF-alfa; antiflogistika; Anti-Inflammatory Agents; Fruit; flavanony